A Novel Torque Controller with Direct Flux Control for Permanent Magnet Synchronous Motor. Issue 1 (July 2017) - Chu, Hongqing; Chen, Hong; Gao, Bingzhao; Zhao, Haiyan
Abstract: Permanent-magnet synchronous motors (PMSMs) are expected to generate a desired torque with high dynamic performance in most traction drive applications. The limitation of current and dc link voltage of a given inverter impact the maximum torque generating capability and the maximum speed with rated torque capability. The paper designs a torque controller directly from a coupling system model for PMSM by using a triple-step nonlinear method, in which the air gap flux control is considered explicitly. From the application point of view, the robustness analysis is discussed for the proposed controller. Finally, the proposed control scheme is carefully verified by simulations. The simulation results show that the proposed nonlinear triple-step controller has a comparative control performance with a widely used controller, and also show that the transition from the constant-torque operation region to the constant-power operation region is straightforward and effective during flux-weakening control.